Two-dimensional heat conduction in the laminate with the functionally graded properties = Dwuwymiarowe zagadnienie przewodnictwa ciepła w laminacie o funkcyjnej gradacji własności - Radzikowska, Alina; Wirowski, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The object of the contribution is the classical Fourier heat conduction in the laminate with functionally graded properties. The laminate is made of two conductors, nonperiodically distributed as laminas along one direction. A macrostructure of the laminate is assumed to be functionally graded along this direction. In order to analyse heat conduction, the tolerance averaging technique is used.
Keywords: przewodzenie ciepła; laminat złożony; funkcyjna gradacja właściwości; technika tolerancyjnego uśredniania; heat conduction; functionally graded laminates; tolerance modelling